Pembuatan Busana Pesta dengan Lengan Pointy - Hidayah, Maimunah Nurul; Budiastuti, Emy (Institut Seni Indonesia Yogyakarta, 2025)
Cultural diversity in Indonesia, one of which is Rumah Gadang is a source of ideas in the creation of party clothes so that party clothes with pointy sleeves are created. This research aims to explore the creation of party fashion with pointy sleeves by using a work creation method consisting of three stages: exploration stage, design stage and realization stage. The exploration stage was carried out to find the source of ideas for making party clothes which were expressed in the form of a moodboard. The planning stage is by making a fashion design that is manifested in the form of pictures or visuals. The realization stage by realizing the results of the party dress design into real party clothing. The result of the research is party clothes with pointy sleeves that are unique, innovative, more modern but also have cultural value. Party clothes that integrate cultural elements in the form of Rumah Gadang's gonjong roof into the shape of pointy sleeves offer a solution to party clothing needs with a more creative design and give a new dimension to party clothes so that they make them more attractive. The pointy sleeve design of party clothes by combining traditional songket materials is able to encourage designers and fashion industry players to continue to innovate to create fashion that is not only modern but also has high cultural and aesthetic value.ABSTRAKKeanekaragaman budaya di Indonesia, salah satunya Rumah Gadang menjadi sumber ide dalam penciptaan busana pesta sehingga terciptalah busana pesta dengan lengan pointy. Penelitian ini bertujuan untuk mengeksplorasi penciptaan busana pesta dengan lengan pointy dengan menggunakan metode penciptaan karya yang terdiri dari tiga tahapan : tahap eksplorasi, tahap perancangan dan tahap perwujudan. Tahap eksplorasi dilakukan pencarian sumber ide pembuatan busana pesta yang dituangkan dalam bentuk moodboard. Tahap perancangan dengan membuat rancangan busana yang diwujudkan dalam bentuk gambar atau visual. Tahap perwujudan dengan mewujudkan hasil rancangan busana pesta menjadi busana pesta sesungguhnya. Hasil penelitian yaitu busana pesta dengan lengan pointy yang unik, inovatif, lebih modern tetapi juga memiliki nilai budaya. Busana pesta yang mengintregasikan elemen budaya berupa atap gonjong Rumah Gadang ke dalam bentuk lengan pointy menawarkan solusi kebutuhan busana pesta dengan desain yang lebih kreatif dan memberikan dimensi baru pada busana pesta sehingga menjadikannya lebih menarik. Desain lengan pointy pada busana pesta dengan memadukan bahan tradisional songket mampu mendorong desainer dan pelaku industri fashion untuk terus berinovasi menciptakan busana yang tidak hanya modern tetapi juga memiliki nilai budaya dan estetika yang tinggi.